Dynamic Simulation Analysis of High Speed Gear Transmission Considering Load and Error Excitation - Zhang Hanlin; Zhi Yanfeng; Zhang Liyong; Wang Changlu; Ding Jun; Wang Kai; Li Chengyu; Jiang Yehu; Zhao Jun (Jixie chuandong)
The dynamic characteristics of high speed gear transmission under high speed conditions have an important influence on the reliable operation of equipment. The gear pair model is established, the dynamic characteristics of high-speed gear drive are analyzed, and the dynamic simulation is carried out under the condition of dynamic excitation of gears. The results show that the fluctuation amplitude of angular velocity increases respectively by 6.12% and 3.46%, after the driving gear is moved by 0.2 mm in the axial direction and 0.15° in the vertical direction. The fluctuation amplitude of the contact force increases respectively by 0.58% and 4.56%. The axial displacement error has a greater influence on the angular velocity, and the angle error has a greater influence on the contact force. When the acceleration time increases from 5 seconds to 10 seconds, the fluctuation amplitude of angular velocity decreases by 10.7% and the standard deviation of angular velocity decreases from 6.974 8 to 6.406. The fluctuation amplitude of contact force increases by 0.58%. After the load increases from 1 000 N·m to 1 626.75 N·m and 2 000 N·m, the standard deviation of angular velocity decreases from 6.974 8 to 4.774 75 and 4.749 45, the fluctuation amplitude of contact force increases respectively by 4.3% and 4.25%, and the rated load is more stable than the gear transmission under light load. The difference of angular velocity and contact force fluctuation is not obvious in the case of heavy load.